Multi-Sectoral Village Collaboration to Increase the Potential of Tourism Destinations in Kertayasa Village, Cijulang District, Pangandaran Regency - Ina Agustiana; Kiki Endah; Rindu Garvera (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2025)
Tourism is a strategic sector for boosting the village economy. Kertayasa Village, Cijulang District, Pangandaran Regency, has significant tourism potential, both in terms of nature and culture. However, this potential has not been optimally managed due to a lack of synergy between the parties involved. This study aims to analyze multi-sectoral village collaboration in enhancing the potential of tourist destinations in Kertayasa Village. This research used a qualitative descriptive method. Data were collected through interviews, observation, and documentation. Informants came from the village government, tourism stakeholders, local communities, academics, business actors, and the media. The results indicate that although collaboration between the pentahelix elements has been established, it has not been optimally implemented. Institutional strengthening, capacity building, and integrated tourism planning and governance are needed to ensure sustainable development of tourism potential. Keywords: Collaboration, Multi-Sectoral, Tourism Village, Pentahelix, Tourism Development